Pengaruh Opini Audit, Reputasi KAP, Ukuran Perusahaan, Solvabilitas, Profitabilitas, Kompleksitas Operasi, Dan Pergantian Auditor Terhadap Audit Delay (Study Empiris Pada Perusahaan Consumer Goods Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Erfan Muhammad; Dewi Retno Puspita; Sukron Mamun (DPPM Universitas Pelita Bangsa, 2023)
This study aims to analyze the effect of audit opinion, KAP reputation, company size, solvency, profitability, company complexity, auditor replacement on audit delay in consumer goods companies listed in the Indonesia Stock Exchange 2016-2020. Data collection and processing were carried out quantitatively using multiple linear regression analysis techniques. The results of this study indicate that there are four factors that affect Audit Delay, such as audit opinion variables, KAP reputation, profitability, and auditor replacement. The variables that have no effect on Audit Delay are the. Company size, solvency, and the complexity of operating variables.